Assessment of the capability to adopt a healthy lifestyle: insights into gender, socioeconomic factors, perceived health, and regional variations - Alenzi, Ebtihag O.; Alqahtani, Wasan Ibrahim; Altwegri, Milan Adeeb; Alhelal, Sadeem Mobark; Alyami, Wadha Ahmad; Almohana, Danah Mohana; Aldrees, Reem Rashed; Alnashar, Rona Shagran; Almugizel, Batool Hussain; Alshabanat, Noura Mohammed; Alzahrani, Ghada Ali (Frontiers in Public Health, 2025)
BackgroundMaintaining a healthy lifestyle, including proper nutrition and physical activity, is essential for reducing non-communicable diseases (NCDs). However, literature lacks sufficient insight into the factors influencing individuals’ ability to adopt healthy lifestyles. Therefore, this study aimed to examine the factors affecting healthy lifestyle adoption among adults, focusing on sociodemographic aspects, regional variations, and health determinants.MethodsA cross-sectional study was conducted between February and March 2023 using convenient sampling, resulting in 999 adult participants. A validated and self-administered questionnaire, including sociodemographic data, health status, and the validated Arabic version of the Capability Assessment for Diet and Activity (CADA) scale, was distributed. Inferential statistics were reported using bi-variate analyses and multivariate regression.ResultsThe capability to adopt a healthy lifestyle was 3.28, with scores for physical activity and diet at 3.3 and 3.27, respectively. Bivariate analyses revealed significant associations of age, educational level, income, housing type, region, weight, and perceived physical and psychological health status with the capability to adopt a healthy lifestyle. In adjusted analyses, males had lower diet scores (β = −0.36, p = 0.026) than females. Participants with incomes below 7,000 SR had lower total CADA scores (β = −0.36, p = 0.064) and lower physical activity scores (β = −0.43, p = 0.026) than those earning >25,000 SR. Participants residing in family houses or duplexes had higher total CADA scores than those in smaller properties. Participants in central regions had significantly higher scores for adopting healthy lifestyles (β = 0.46, p = 0.040) than those in other areas. Overweight had higher total CADA scores (β = 0.58, p = 0.011) and healthier diet scores (β = 0.64, p < 0.01) than extremely obese. Furthermore, positive perceptions of physical and/or mental health were linked to higher scores in adopting healthy lifestyles.ConclusionThe findings underscore the impact of gender, income, housing type, region, and perceived health status on individuals’ ability to engage in physical activity and adopt a healthy diet. Thus, health strategies that address these differences could enhance the adoption of healthier lifestyles and reduce the prevalence of lifestyle-related diseases in the population.